2016
DOI: 10.3390/toxins8120355
|View full text |Cite
|
Sign up to set email alerts
|

Fast Screening of Antibacterial Compounds from Fusaria

Abstract: Bio-guided screening is an important method to identify bioactive compounds from fungi. In this study we applied a fast digital time-lapse microscopic method for assessment of the antibacterial properties of secondary metabolites from the fungal genus Fusarium. Here antibacterial effects could be detected for antibiotic Y, aurofusarin, beauvericin, enniatins and fusaric acid after six hours of cultivation. The system was then used in a bio-guided screen of extracts from 14 different Fusarium species, which had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 42 publications
0
30
1
5
Order By: Relevance
“…This was performed with a checkerboard analysis ( 31 ), which showed the MICs of bikaverin and beauvericin to be 60 (157 µM) and 240 (306 µM) µg/ml, respectively. The bikaverin MIC was higher than that reported for Escherichia coli of 65 µM ( 27 ), and the beauvericin MIC was higher than the reported 32 µM for Lactobacillus acidophilus and Staphylococcus aureus ( 28 ). The interaction between the metabolites was characterized as additive due to its fractional inhibitory concentration (FIC) index value of 0.708 ( Fig.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…This was performed with a checkerboard analysis ( 31 ), which showed the MICs of bikaverin and beauvericin to be 60 (157 µM) and 240 (306 µM) µg/ml, respectively. The bikaverin MIC was higher than that reported for Escherichia coli of 65 µM ( 27 ), and the beauvericin MIC was higher than the reported 32 µM for Lactobacillus acidophilus and Staphylococcus aureus ( 28 ). The interaction between the metabolites was characterized as additive due to its fractional inhibitory concentration (FIC) index value of 0.708 ( Fig.…”
Section: Resultscontrasting
confidence: 56%
“…The induction of both bikaverin and beauvericin in response to the bacterial signal ralsolamycin, coupled with the accruement of bikaverin in chlamydospores, suggested a possible evolved function of these metabolites toward protection from the endosymbiotic bacteria. Indeed, both metabolites have been previously shown to be antibacterial ( 27 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, 20 years ago, Becker et al [ 33 ] used culture techniques and observed no inhibition of bacterial growth including Lactobacillus acidophilus , Lactobacillus johnsoni , Lactobacillus plantarum and Lactobacillus reuteri . Finally, two independent studies [ 34 , 35 ] found no antibiotic effect of FB1, thus excluding an antimicrobial effect to explain a fumonisin-related shaping action on gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 22 naphthoquinones from F. solani and F. oxysporum were examined by Baker and colleagues, of which 12 were antimicrobial against Streptococcus pyogenes and 15 were active against Staphylococcus aureus [ 20 ]. Aurofusarin was shown to inhibit probiotic bacteria, which might shift the gut microbes to a more harmful constitution causing illness and diarrhea [ 21 ]. Also, aurofusarin is cytotoxic, genotoxic, and induces oxidative stress in human colon cells [ 22 ].…”
Section: Introductionmentioning
confidence: 99%